Dive in the flow experience: millennials’ tech-savvy, satisfaction and loyalty in the smart museum - Rongteng (Renata), Zhang; Abd Rahman, Azmawani (Routledge, 2022)
The smart museum, which is the ascendant of the museum industry, has caught academic attention for smart destinations. However, a few studies have examined millennial visitors in the research of smart museums, which are not only the core of the market but also born advantageous to smart technology. Drawing on flow theory and the information system (IS) success model, this study investigated the effect of tech-savvy, information quality and system quality on millennial visitor satisfaction and loyalty towards the smart museum via flow experience. From a quantitative point of view, the experiences of 519 millennial visitors in China were collected, and relationships were tested using partial least squares structural equation modelling (PLS-SEM). The results show that millennials’ tech-savvy, information quality and system quality of smart museums significantly impact visitor satisfaction and loyalty through the mediating effect of flow experience. This study contributes to the current knowledge on smart destination marketing and identifies the effectiveness of the extended model. From these findings, practical implications for museum managers and marketers to promote smart museum development are discussed.